Change-time detection in moving average model based on reversible jump MCMC algorithm - ., Suparman (International Journal of Engineering and Technology, 2019)
A piecewise moving average is a model that is more flexible than the moving average model. If the piecewise moving average is used to model data, the model parameters are unknown. The model parameters include the number of models, model coefficients, and white noise variance. This paper discusses the parameter estimation of the piecewise moving average model. Parameter estimation is done using the hierarchical Bayesian approach. Bayes estimators are calculated using the reversible jump Markov chain Monte Carlo algorithm. The performance of the algorithm is tested using synthesis data. The results showed that the reversible jump Markov chain Monte Carlo algorithm can estimate the parameters of the piecewise moving average model well.Â Â